The Relevance of Language Awareness to Teaching Literature for EFL students - Kurnia Ningsih (Universitas Negeri Padang, 2014)
Language does not simply consist of vocabulary and grammar. There is much more in language that makes it work. It has functions and involves nuances when people use it for communication. Halliday (1985) says learning language means learning” how to mean”. Thus students who learn foreign language should be aware of these factors in order to be able to understand how the native speakers use their language and what they mean. Teaching literature requires students to be aware of the use of language in order to get the meaning in the text. Literary works help them develop their language skills, awareness of language and culture, even critical thinking. This paper discusses how language awareness is relevant to teaching English literature. Both of them require teachers to provide students with experience how to use language in expressing their opinion, sharing ideas, investigating a variety of interpretation’s as well as thinking critically.